2022
DOI: 10.3390/jdb10030033
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Palate in Apert Syndrome

Abstract: Apert syndrome is a rare genetic disorder characterized by craniosynostosis, midface retrusion, and limb anomalies. Cleft palate occurs in a subset of Apert syndrome patients. Although the genetic causes underlying Apert syndrome have been identified, the downstream signaling pathways and cellular mechanisms responsible for cleft palate are still elusive. To find clues for the pathogenic mechanisms of palatal defects in Apert syndrome, we review the clinical characteristics of the palate in cases of Apert synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 111 publications
(152 reference statements)
0
4
0
Order By: Relevance
“…This is likely due to the significant change that takes place when mutating serine, which is a small polar residue, to tryptophan, a bulky aromatic hydrophobic residue. The S252 residue promotes ligand affinity and specificity [ 74 ]. The two most frequent mutations identified in endometrial cancers are FGFR2 S252W and N550K, which are both activating mutations [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the significant change that takes place when mutating serine, which is a small polar residue, to tryptophan, a bulky aromatic hydrophobic residue. The S252 residue promotes ligand affinity and specificity [ 74 ]. The two most frequent mutations identified in endometrial cancers are FGFR2 S252W and N550K, which are both activating mutations [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the multiple mutations that were deemed significant in PIK3CA and TP53 were located at the same place in the primary sequence in each respective gene. The FGFR2 S252W mutation has been previously studied biochemically and shown to impact ligand binding and specificity [ 74 ]. The R130 residue in PTEN is located within the active site pocket and mutation of this residue has been implicated in various diseases and cancers [ 63 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we identified a variant in FGFR2 , c.755C>G (p.(Ser252Trp)), in case 11, which is associated with the development of Apert syndrome (OMIM #101200). Apert syndrome is a rare genetic disorder characterized by an array of clinical features, including craniosynostosis, midface retrusion, and limb anomalies ( Willie et al, 2022 ). A cleft palate is present in a subset of Apert syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt1-Cre;pMes-caBmpr1a mice showed reduced proliferation and ectopic cartilage formation at the palatal mesenchyme ( Li et al, 2013 ). NC-specific deletion of Tak1 in mice ( Wnt1-Cre;Tak1 fl/fl mice) develops cleft palate association with a higher level of fibroblast growth factor (FGF) signaling that is a known causative reason for Apert syndrome, a subset of patients with the syndrome develops cleft palate ( Song et al, 2013 ; Willie et al, 2022 ). We found that NC-specific expression of caBmpr1a with deletion of Tak1 in mice ( P0-Cre;caBmpr1a fl/+ ;Tak1 fl/fl mice) develops cleft palate while P0-Cre;caBmpr1a fl/+ mice and P0-Cre;Tak1 fl/fl mice did not develop a cleft palate.…”
Section: Orofacial Cleftmentioning
confidence: 99%